THE IMPORTANCE OF LEARNING MORAL VALUES IN EARLY CHILDREN - Khulusinniyah Khulusinniyah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
As commanded by Allah SWT, of course parents or educators are obliged to educate children from childhood so that they become people of faith and fear of Allah SWT. The early childhood stage is a great initial opportunity to develop a child's personality, which will determine his future. This research is a field study that focuses on the results of data collection from certain informants. Field research can also be seen as a qualitative data collection method, meaning that it is intended to provide an in-depth study of how a social unit works. Results Instilling moral values ​​is very well applied from an early age. To find out the state of the moral values ​​of students in PAUD, researchers conducted interviews with teachers. According to the survey results, the answers were: